Figure of Speech Stylistic Analisys on Song Liryc in Sami Yusuf’s Albums - Molidah Molidah; Imam Qalyubi; Aris Sugianto (English Education Department, 2021)
Abstract: This research aimed to analyze figure of speech Stylistic in Sami Yusuf’s song lyrics. The author is intrigued by the songwriter's lyrics that may occur in the life we live. The purpose of this study is to determine whether or not there are any figure of speech features in Sami Yusuf's song lyrics, as well as to examine the meaning of the song lyrics found in Sami Yusuf's song lyrics. Content analysis was a part of this study. The method used in this study is descriptive qualitative research, and the design is qualitative research. The data was gathered through library research. The researcher is the research instrument since he or she is the main instrument in this study who collects and evaluates the data. After finishing the investigation, the researcher discovered that the most common figure of speech is personification, which has 14 data, and the least common figure of speech is paradox, which has one data. Metaphor (4 data), simile (7 data), synecdoche (10 data), metonymy (5 data), symbol (4 data), and hyperbole (5 data) are some of the other data collected. In other cases, the researcher found no figures of speech like allegory, apostrophe, understatement, or linguistic irony. The connotations of figure of speech utilized in Sami Yusuf's song lyrics are varied. Keywords: figure of speech, song lyric, stylistic